Empowerment Theory For Performance Improvement: A Literature Study - Teguh Setiawan Wibowo; Endri Haryati; Mochamad Fatchurrohman; Shobikin Shobikin; Damarsari Ratnasahara Elisabeth (International Journal of Economics, Business and Innovation Research, 2024)
Empowerment is a construct that connects individual strengths and competencies, natural helping systems and proactive behavior with organizational policies and changes. Empowerment refers to the provision of authority, strength and knowledge needed by a person as a worker to help him/her overcome obstacles experienced in the organization. If a person as a worker or member of an organization has good Empowerment, it can encourage his/her enthusiasm to gain abilities or competencies and knowledge enabling him/her to overcome obstacles in the life of the organizational environment as a place to work and help develop himself/herself or his/her organization in the future. This study aims to determine the variables related to Empowerment. This study also presents a literature study using a systematic literature review of relevant publications and as a result of this process, 10 journal articles were included, then, checking bibliographic references to validate questions and avoid potential omissions. Empowerment was found to be a moderating variable. There are several prominent variables that influence Empowerment such as training, incentives/rewards, delegation of authority, and managerial experience. In addition, other variables influenced by Empowerment such as trust, leadership style, and organizational policies. The implication for practitioners is to be able to understand things related to Empowerment in order to further improve organizational performance.